2019
DOI: 10.5888/pcd16.180618
|View full text |Cite
|
Sign up to set email alerts
|

A Faith-Based Intervention to Reduce Blood Pressure in Underserved Metropolitan New York Immigrant Communities

Abstract: Minority populations, including Asian Americans, face disparities in hypertension compared with non-Hispanic whites. This underscores the need for culturally adapted programs in settings that reach Asian American communities, such as faith-based organizations. We worked collaboratively with community partners to culturally adapt and implement an evidence-based community blood pressure monitoring program for Asian Americans (Asian Indians, Koreans, Filipinos, and Bangladeshis) in metropolitan New York during 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…Overall, 11 studies representing 10 distinct hypertension interventions were identified (Table 1 ). Populations of focus included immigrants of African [ 37 ••, 38 ], Filipino [ 39 ••, 40 ], Hispanic or Latino (unspecified nationalities) [ 41 , 42 ••, 43 ], Chinese [ 44 ], South Asian [ 45 ••, 46 ], and multiple Asian [ 47 ••] descents. Most studies ( n = 6) did not involve a control group and employed a pre-post-quasi experimental study design [ 37 , 38 , 42 ••, 43 , 44 , 47 ], including one stepped-wedge quasi-experimental intervention [ 45 ••, 46 ] and two randomized controlled trials [ 39 ••, 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Overall, 11 studies representing 10 distinct hypertension interventions were identified (Table 1 ). Populations of focus included immigrants of African [ 37 ••, 38 ], Filipino [ 39 ••, 40 ], Hispanic or Latino (unspecified nationalities) [ 41 , 42 ••, 43 ], Chinese [ 44 ], South Asian [ 45 ••, 46 ], and multiple Asian [ 47 ••] descents. Most studies ( n = 6) did not involve a control group and employed a pre-post-quasi experimental study design [ 37 , 38 , 42 ••, 43 , 44 , 47 ], including one stepped-wedge quasi-experimental intervention [ 45 ••, 46 ] and two randomized controlled trials [ 39 ••, 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Populations of focus included immigrants of African [ 37 ••, 38 ], Filipino [ 39 ••, 40 ], Hispanic or Latino (unspecified nationalities) [ 41 , 42 ••, 43 ], Chinese [ 44 ], South Asian [ 45 ••, 46 ], and multiple Asian [ 47 ••] descents. Most studies ( n = 6) did not involve a control group and employed a pre-post-quasi experimental study design [ 37 , 38 , 42 ••, 43 , 44 , 47 ], including one stepped-wedge quasi-experimental intervention [ 45 ••, 46 ] and two randomized controlled trials [ 39 ••, 41 ]. Diverse regions of the U.S. with large populations of immigrants were represented, including California [ 37 ••, 44 ], Texas [ 38 , 42 ••], Pennsylvania [ 39 ••], South Carolina [ 41 ], Florida [ 43 ], and New York [ 40 , 45 ••, 46 , 47 ••].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1). [30][31][32][33][34] The intervention evaluation questions were developed based on the Social Cognitive Theory with a focus on questions related to how the intervention addressed self-management strategies, including self-efficacy and behavior change. 35,36 The interview guide was amended as new concepts were identified in order to further explore and understand emerging theoretical constructs.…”
Section: Assessmentmentioning
confidence: 99%